Multi-stakeholder collaboration in urban transport: state-of-the-art and research opportunities - Gonzalez-Feliu, Jesus; Pronello, Cristina; Salanova Grau, Josep Maria (Transport, 2018)
Transport systems are undergoing a change of paradigm that focuses on resource-sharing and collaboration of multiple and diverse stakeholders. This paper aims to present a state-of-the-art on the main research issues of multi-stakeholder collaboration in urban transport and address the main contributions of the Special Issue on Collaboration and Urban Transport to the field. To that end, it seems necessary to identify and address the complexity of the relations of the stakeholders in the field, beyond the traditional classification of private and public stakeholders. A functional classification of urban stakeholders related to the different land uses is proposed a refer to space users and space organizers, each with several sub-categories. Furthermore, the collaboration among those stakeholders can take different forms and can be developed at different levels: transactional, informational and decisional. Thus, the main research topics regarding multi-stakeholders’ collaboration are defined as: partnerships, resource sharing, resource pooling and Mobility-as-a-Service (MaaS) systems. A set of papers in this special issue focus on Urban Consolidation Centres (UCCs), partnerships in transport under a general perspective, multi-stakeholder cooperation and its barriers, collaborative decision-making, traffic prediction and urban congestion. In the papers, which deal with the field of multi-stakeholder collaboration in urban transport, there is a predominance on the use of surveys, but also a focus on data-driven techniques. As a result, this special issue contributes not only to the theoretical aspects, but adds value to technical and methodological issues.